CATEGORY OF PUBLIC INTEREST IN DETERMINING THE BOUNDARIES OF ADMINISTRATIVE REASONING - VDOVICHEN, VITAL (Ehrlich’s Journal, 2023)
The article analyzes the legal category of “public interest” in order to determine its role in the mechanism of administrative discretion. At the same time, it is necessary to take into account the binding of public needs as the main function of the state. Based on the study of the decision-making process by the authorized entity, we demonstrate the existence of a criterion that exerts undeniable direct influence and, at the same time, serves as a qualitative guide in the exercise of their powers – public interest as a factor determining and setting limits of administrative discretion. In the science of administrative law, the discussion of the content of the categories “public interest” and “administrative discretion” are fundamental theoretical and applied concepts that are constantly relevant. It is established that the correlation between the categories of “public interest” and “administrative discretion” is indisputable, because the study of the implementation of administrative discretion is not possible without the establishment and analysis of the subjective factor. At the same time, the public interest is the main qualitative criterion for determining the limits of public administration options for possible behavior – administrative discretion. The author substantiates that “publicity” includes accessibility and opportunity for citizen participation in the life of the state. The state acts as an instrument for meeting public needs through the right to choose the relevant executive bodies and participate in their activities; transparency and openness of their functioning; public control over the activities of public administration bodies and their officials, over the observance of the constitutionally defined and enshrined interests of society, the rights and freedoms of citizens. The affiliation of law enforcement to the elements of the legal system is explained by the defining legal significance of individual legal activities carried out by the competent public administration. Activities of this kind make it possible to distinguish between lawmaking and individual legal regulation. The choice of permissible or necessary behavior becomes possible through a clear definition of subjective rights and subjective civil obligations, which is due to the content of public law. Entering into public law relations to satisfy the public interest, the public administration chooses appropriate behavior that would meet the requirements of the law. Therefore, such entities are obliged to apply only those forms of administrative discretion that are determined by law (law), to choose legitimate alternatives that fall within their competence. The key feature of the limits of administrative discretion in the activities of public administration bodies is the framework of permissible freedom of law enforcement in the choice of options by the subject of law enforcement. The public interest in administrative discretion is the desire of authorized entities to ensure the lawful realization of their competence, to take actions aimed at meeting the needs, protection of rights and fulfillment of obligations imposed on them by the Constitution and state legislation. If the public interest as a limit to the application of administrative discretion is not fully or inadequately defined by the legislator, it affects the entire rule-making process, leads to unstable legislative policy and frequent changes in legal norms.